Determinan Kepatuhan Wajib Pajak dari Pemahaman Peraturan Perpajakan, Sanksi Perpajakan, dan Kualitas Pelayanan Fiskus - Kamelia Putri; Nera Marinda Machdar (Jurnal Riset Ekonomi dan Akuntansi, 2025)
The largest source of income used to support all government activities is from taxes, ranging from employee salaries to infrastructure development. With the increasing number of taxpayers, both individual taxpayers and organizational taxpayers, the tax sector can anticipate increased revenue. This study aims to find and examine the effect of understanding tax regulations, quality of tax services, and tax sanctions on taxpayer compliance. This study uses the literature review method to analyze the reasons behind the explanatory variables. The theory behind this study is the theory of compliance and attribution. The results of the study show that the relationship between understanding tax regulations, quality of tax services, and tax sanctions on taxpayer compliance varies, so that a clear agreement has not been reached. This study provides a picture based on existing facts for further research using the variables of understanding tax regulations, quality of tax services, and tax sanctions.